A Paraurethral Aggressive (Deep) Angiomyxoma - Daniel York; Smera Saikumar; Pavan Patel; Christian Edwards; Geossette Garcia; Hyder Naqvi (Hindawi Limited, 2022)
Background. Aggressive angiomyxomas (AAs) are rare mesenchymal tumors that are histologically composed of myxoid stroma and vasculature. AAs are typically located in the pelvis and perineum and occur more frequently in females of reproductive age. Case Presentation. In this report, we outline a patient who had a paraurethral tumor with histopathology showing a circumscribed hypocellular lesion with myxoid stroma and abundant vasculature, consistent with the diagnosis of aggressive angiomyxoma. The mass was excised with resolution of symptoms and the patient was advised to continue close follow-up with her gynecologist and endocrinologist to monitor for recurrence. Conclusion. Due to its rarity, aggressive angiomyxomas are often misdiagnosed as cysts, hernias, lipomas, or cancerous lesions. Although benign, close follow-ups are crucial to monitor for recurrences or metastasis.